Aktivitas Santap dan Minum Generasi Z pada Media Sosial Instagram - Irwanto Irwanto; Laurensia Retno Hariatiningsih (MediaTor (Jurnal Komunikasi), 2019)
This study aims to reveal more about the use of social media especially Instagram (IG) in the activities of eat and drink in Generation Z through communication review. The method used in this research is descriptive qualitative research. Data collected through in-depth interviews, observation and literature study. Determination of research subjects is based on the choice of generation Z in the span of 24 years and below. In this research the object of research reveals deeper motives in using IG for dining activities by generation Z. By revealing more about the generation Z dining activities, researchers can find deeper motives carried out by Generation Z. After making observations, conducting interviews and supporting by literature study researchers have found that the photos uploaded by generation Z essentially not the intended food or beverage, but only the sign that represents  the food and beverage earlier. The process of capturing food and beverage carried out is a construction activity in accordance with the interest of the realization of the communication motive. As a new media, social media still has various phenomena to be explored further. There are quite a lot of social media users in Indonesia with high heterogeneity.